Effect of phenolic acids on the antioxidant system of tomato plants (Solanum lycopersicum Mill.) - Zárate-Martínez, William (2021)
Introduction. Phenolic acids belong to the group of phenolic compounds, their synthesis and concentration in plants increases when they are under biotic or abiotic stress conditions. Objective. To evaluate the effect of phenolic acids on the enzymatic and non-enzymatic antioxidant defense system in tomato plants subjected to biotic stress. Materials and methods. The experiment was carried out from March to December 2016, in Saltillo, Mexico. A tomate crop Saladette type of the Rio Fuego variety (Solanum lycopersicum Mill.) was stablished. Tomato plants inoculated with Clavibacter michiganensis subsp. michiganensis (1X105 CFU ml-1) were foliar sprayed with phenolic acids at a dose of 1 kg ha-1 with the Defens Gr® product (IA: phenolic acids 10 000 ppm). Leaves were sampled at 15, 31, and 92 days after the transplantation (ddt) and fruits at 90 ddt. Six treatments were used: 1) absolute control (T0), 2) application of phenolic acids before the inoculation with Clavibacter (AFA), 3) application of phenolic acids after inoculation with Clavibacter (AFD), 4) application of phenolic acids before and after inoculation with Clavibacter (AFAD), 5) only application of phenolic acids (AF), and 6) only inoculation with Clavibacter (Cmm). Results. The application of phenolic acids intervened in the activity of enzymatic and non-enzymatic antioxidants. A higher antioxidant capacity was found in leaf than in fruit, which was determined by ABTS (2,2’-azino-bis (3-ethylbenzothiazolin-6-sulfonic acid)) and DPPH (1,1-diphenyl-2-picrilhydrazil). The inoculation of tomato plants increased the activity of catalase and phenylalanine ammonium lyase enzymes in leaf; in addition, there was reduction of superoxide dismutase enzyme activity and total phenol content. Conclusion. Phenolic acids intervened in the enzymatic defense mechanisms of the plant and reduced the stress levels caused by inoculation.